ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA SEKTOR HOTEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Rahma Wanti; Maya Syaula (Perkumpulan Doktor Indonesia Maju, 2022)
This study aims to determine financial performance based on profitability ratios and liquidity ratios which are calculated using the current ratio and quick ratio in the hotel sector listed on the Indonesia Stock Exchange for the 2018-2022 period. This research is a quantitative research, where this research is a descriptive approach. Data collection techniques in this study are documentation with secondary data sources, namely financial reports from from 2018 to 2022 which includes a balance sheet and income statement. The ratio analysis technique used is the Profitability Ratio, namely Net Profit Margin and Return On Assets. While the Liquidity ratio uses the Current Ratio and Quick Ratio. Based on the results of the analysis and discussion, the financial performance of hotel sub-sector companies listed on the IDX for the 2018-2022 period is measured using profitability ratios on Net Profit Margin (NPM) and Return On Assets (ROA) indicating that the majority of the average NPM and ROA have not reached industry average standards. Meanwhile, in terms of liquidity ratios, as measured using the Current Ratio and Quick Ratio, it shows that the majority of CR and QR averages have exceeded industry average standards